Islamic Education Values In Extracurricular Activities - Sutisna, Ujang; Rohman, Miftahur; Gumanti, Nilam Zelfa Rani (Universitas Islam Negeri Raden Intan Lampung, 2023)
the internalization of Islam education values in extracurricular scouting activities will make humans who are able to balance the needs of the world and the hereafter as well as religious science and general science. Internalization can produce high-quality education, namely education that can provide knowledge, both religious science and universal general science, mastery of modern technology, skills, experience, broad relationships, and noble morals. The purpose of this research is to describe the implementation of the internalization of Islamic education values through extracurricular scouting activities at SMP Negeri 23 Bandar Lampung. The method used in This research is qualitative and descriptive. Data collection techniques The data collection techniques used are observation, interview, and documentation. The results showed the internalization of Islamic educational values contained in extracurricular scout activities, namely the value of akidah, worship, and morals, namely through camp activities and scout training. in which there are congregational prayer activities, kultum, spiritual inspiration, and reading prayers before and after scout activities or training. prayers before and after scouting activities or training, the inauguration of councils and signs of general proficiency in grasshoppers, and evaluation of activities